Efficacy Test of Cyperus rotundus L., and Ageratum conyzoides L Bioherbicide for Weed Control and Their Effects on Baby Corn (Zea mays L.) Yield - Azzahra Farhan; Siwi Hardiastuti E.K; Abdul Rizal A.Z (Jurnal Syntax Transformation, 2025)
Baby corn production in Indonesia continues to decline due to weed competition with corn plants. Weeds are the main competitors in the process of absorbing nutrients, water, light and space to grow. Weed control using synthetic herbicides can be reduced by using weed extracts as bioherbicides. This research aims to determine the effect of extracts from nutgrass (Cyperus rotundus L.), and whiteweed (Ageratum conyzoides L.) in controlling weeds and determining their effect on baby corn crop yields. The research has been carried out in fields on Brengosan, Sumberdadi, Mlati District, Sleman Regency, Special Region of Yogyakarta in March - May 2025. The research used a Randomized Complete Block Design with 7 treatments and 3 replications, namely without bioherbicides, 20% nutgrass extract, 40% nutgrass extract, 60% nutgrass extract, 20% whiteweed extract, 40% whiteweed extract, and 60% whiteweed extract. The resulting data were analyzed using 5% ANOVA and further tested using 5% LSD. The results showed that the treatment of 40% nutgrass extract had the highest weed control effectiveness, which was 77.97%.